(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The purpose of this research is to study the availability and application of innovative marketing strategies in industrial companies in the Syrian Arab Republic, through a study of the Syrian Arab Company for Electronic Industries, by evaluating the availability of the four dimensions of innovative marketing (product innovation, pricing innovation, distribution innovation, and promotion innovation). The descriptive method was adopted by referring to previous studies and accurately describing the study variables. The questionnaire was used as a tool for collecting primary data, by distributing the questionnaire to a convenient random sample of 99 company customers. The t-test for one sample was used as one of the tests necessary to achieve the objectives of the study. A number of results were reached, including: • There was a high degree of use and application of product innovation by the Syrian Arab Company for Electronic Industries. • There was a high degree of application of pricing innovation by the Syrian Arab Company for Electronic Industries. • There was a high degree of application of distribution innovation by the Syrian Arab Company for Electronic Industries. • There was a high degree of application of promotion innovation by the Syrian Arab Company for Electronic Industries